Characteristics of black South African adult and adolescent women who gave premature birth to growth-restricted infants at Kalafong hospital, Gauteng - Gilfillan, Marlene (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--University of Stellenbosch, 2006.